P144 Correlation between clinical, endoscopic, histological activity scores in a cohort of patients with ulcerative colitis: a prospective study. (25th January 2019) - Neri, B; Romeo, S; Zorzi, F; De Cristofaro, E; Calabrese, E; Grasso, E; Palmieri, G; Biancone, L
Abstract: Background: The relationship between clinical, endoscopic and histological scores used in ulcerative colitis (UC) is debated. Primary aim was to assess, in a prospective study, the correlation between clinical, endoscopic, and histological scores of activity in a cohort of UC patients undergoing colonoscopy. Secondary aim was to assess the role of histological scores in clinical practice. Methods: From February 2016 to February 2017 UC patients undergoing colonoscopy according to clinical indication were enrolled. Inclusion criteria: (1) diagnosis of IBD; (2) age> 18, <80 years; (3) regular follow-up; (4) indication for colonoscopy. During colonoscopy ≥2 biopsies were taken from ≥1 macroscopically involved area and, possibly, from ≥1 uninvolved area. All colonoscopies were performed by the same IBD-dedicated gastroenterologist. Clinical activity was assessed with Mayo partial score (activity ≥3), 1 endoscopic activity with the Mayo endoscopic score (activity ≥2). 1 Histological activity was assessed by the same IBD-dedicated pathologist using the Geboes Simplified Score for UC (activity ≥3.1). 2 Scores were blindly assessed. Follow-up was planned at 1 year. Data expressed as median [range]; coefficient of correlation; T-test. Results: UC cohort included 91 patients (M 52 [57%], age 51 [24–80] years, UC duration 15 years [1–48] years). UC extent was n (%): pancolitis 43(47%), left sided 25(28%), proctitis 22(25%) patients. The day of colonoscopy UC was clinically active in 16 (18%), inactive in 75 (82%) patients. Endoscopic activity was observed in 46(51%) patients (Mayo score: [ n ]: 0[17];1[28]; 2[21], 3[25]). In UC, microscopic activity (GSS ≥ 3.1) was observed in 39/91 (43%) patients: 5 of these 39 patients were in endoscopic remission. Significant correlation was observed between clinical vs. endoscopic scores ( r = 0.486; p < 0.0001); clinical vs. histological scores ( r = 0.35; p < 0.0001). At 1-year clinical follow-up data were available in 77 UC patients (75%). In 1 year, UC has been clinically active in 24 (31%) patients, inactive in 53 (69%) patients. 11/24 (46%) patients were clinically active at baseline, 15/24 (63%) patients endoscopically and 16/24 (67%) patients histologically. Of the 5 patients in endoscopic remission and histological activity at baseline, 1 had a clinical relapse. Conclusions: In a prospective study, significant correlation was observed between clinical, endoscopic and histological activity in UC. Histological activity observed in UC patients in endoscopic remission may represent a predictive marker of clinical relapse. Correlation between clinical and endoscopic, endoscopic and histological, clinical and histological activity scores References 1. Schroeder KW, Tremaine WJ, Ilstrup DM. Coated oral 5-aminosalicylic acid therapy for mildly to moderately active ulcerative colitis. N Engl J Med 1987;317:1625–9. 2. Jauregui-Amezaga A, Geerits A, Das Y et al . A simplified Geboes score for ulcerative colitis. J Crohns Colitis 2017;11:305–313.